Mercury Metal Absorption using Ethylene Diamine Tetraacetic Acid Intercalated Carbon - Indah, Dahlia Rosma; Hatimah, Husnul (Hydrogen: Jurnal Kependidikan Kimia, 2023)
Silver craft waste contains hazardous metals, one of which is mercury metal. If high concentrations of mercury waste are disposed of without treatment, this waste seeps into the soil and pollutes residential water sources because mercury metal is difficult to decompose. Mercury poisoning can cause nerve reactions such as difficulty speaking, blurred vision, muscle weakness, paralysis, impaired sense of taste, and shortness of breath. This research was conducted as an effort to reduce mercury metal levels in silver craft waste in Central Lombok Regency. The method of waste treatment is by adsorption method utilizing carbon bagasse modified with EDTA. The first step is to first determine the level of mercury metal in silver craft wastewater in Central Lombok. Furthermore, wastewater is contacted with EDTA-intercalated bagasse carbon. Making intercalated carbon bagasse consists of 3 stages, namely first dehydration by burning bagasse until it turns into carbon, second carbonation is heating temperature 500ÂºC, carbon results are sifted 100-200 mesh and third, intercalation is by soaking 100 grams of carbon in 250 mL EDTA solution 10% stirred for 6 hours. After that the carbon is dried at a temperature of 50ÂºC. A total of 2 grams of intercalated bagasse carbon that has been made is put into 25 mL of wastewater samples. The sample was stirred at contact time variations of 30, 60, 90, 120 and 150 minutes using a stirer. The optimum time obtained is used to calculate the efficiency of reducing mercury metal levels, namely calculating the difference in mercury metal levels before adsorption and after adsorption using EDTA intercalated carbon baggase. Mercury metal levels were analyzed using an Atomic Absorption Spectrophotometer (SSA). From the study, it was found that the mercury metal content in the sample was 50.6398 ppb. The optimum contact time in mercury metal adsorption is at a contact time of 120 minutes which results in an optimum adsorption efficiency in mercury metal of 70.55%.